Surface mixing of products and substrate of PLA2 in enzyme-free mixed monolayers reproduces enzyme-driven structural topography - de Tullio, Luisina (2013)
It was proposed that topographic changes in lipid monolayers hydrolyzed by lipolytic enzymes such as Phospholipase A2 (PLA2) are a consequence of enzyme activity at the surface. Lateral packing defects that arise from lipid phase coexistence were suggested as places at which PLA2 activity is preferably localized. Our work employs a method for mixing two lipid monolayers in order to simulate lipid mixing of products and substrate at the surface in the absence of enzyme. In such enzyme-free mixed films, a topographic pattern similar to that actively generated by PLA2 is observed. The main conclusion from our experiments is that mixing–demixing properties of substrate and products generated by PLA2 can determine the evolution of the surface topography.